Dissect Relationships Between Gene Co-expression and Functional Connectivity in Human Brain - Zhang, Xue; Xie, Yingying; Tang, Jie; Qin, Wen; Liu, Feng; Ding, Hao; Ji, Yuan; Yang, Bingbing; Zhang, Peng; Li, Wei; Ye, Zhaoxiang; Yu, Chunshui (Frontiers in Neuroscience, 2021)
Although recent evidence indicates an association between gene co-expression and functional connectivity in human brain, specific association patterns remain largely unknown. Here, using neuroimaging-based functional connectivity data of living brains and brain-wide gene expression data of postmortem brains, we performed comprehensive analyses to dissect relationships between gene co-expression and functional connectivity. We identified 125 connectivity-related genes (20 novel genes) enriched for dendrite extension, signaling pathway and schizophrenia, and 179 gene-related functional connections mainly connecting intra-network regions, especially homologous cortical regions. In addition, 51 genes were associated with connectivity in all brain functional networks and enriched for action potential and schizophrenia; in contrast, 51 genes showed network-specific modulatory effects and enriched for ion transportation. These results indicate that functional connectivity is unequally affected by gene expression, and connectivity-related genes with different biological functions are involved in connectivity modulation of different networks.